Operative surprise! A hitherto undiscovered dialysis catheter removed successfully from the external iliac vein during renal transplant - A case report - Nitin Agarwal; Anil Kumar Singh Rana; Manoj Kumar Dokania; Himank Goyal (Indian Journal of Transplantation, 2020)
The incidence of chronic kidney disease (CKD) has reached epidemic proportions in India over the past few decades. One of the reasons is the abnormally high prevalence of diabetes mellitus and hypertension. After conversion to end-stage renal disease, renal replacement therapy (RRT) either as dialysis or renal transplant is critical for survival. Facilities for hemodialysis are also abysmally low; this is compounded by poorly trained personnel in peripheral hospitals. These factors contribute to the poor outcome of CKD patients, even if RRT is initiated. We present a case of a middle-aged man who underwent renal transplant for CKD; during the mobilization of the right external iliac vein, a previously undocumented sequestered dialysis catheter was found in the lumen of the vein. This is probably the first such case in literature and highlights the paucity of optimal hemodialysis facilities in the country. The dilemma of continuing the transplant on the same side versus exploring the left side is also discussed. Timely transplant, preferably preemptive transplant, can mitigate many of the problems of chronic hemodialysis. These problems can arise from access to thrombosis or foreign bodies; preoperative accurate Duplex imaging is essential.